3(1/9)×(1(5/28)-0,3)=1,5-(5/6)×(7-х)
3(1/9)=(28/9)
1(5/28)=(33/28)
0,3=(3/10)
1,5=(15/10)=(3/2)
(28/9)×((33/28)-(3/10))=(3/2)-(35/6)+(5/6)х
(28×11×3)/(28×3×3)-(3×14×2)/(3×3×2×5)=(3×3-35)/6+(5/6)х
(11/3)-(14/15)=(9-35)/6+(5/6)х
(11×5-14)/15=-(26/6)+(5/6)х
(41/15)=-(13/3)+(5/6)х
(5/6)х=(41/15)+(13/3)
(5/6)х=(41+13×5)/15
(5/6)х=(41+65)/15
(5/6)х=(106/15)|×(6/5)
(6/5)×(5/6)х=(106/15)×(6/5)
х=(106×6)/(15×5)
х=(106×2×3)/(5×3×5)
х=212/25
х=8(12/25)=8,48
Проверка:
3(1/9)×(1(5/28)-0,3)=1,5-(5/6)×(7-х)
(28/9)×((33/28)-(3/10))=(3/2)-(35/6)+(5/6)х
(5/6)х=(106/15)
(5/6)×(212/25)=(106/15)
(5×2×106)/(2×3×5×5)=(106/15)
(106/15)=(106/15)-истина.
Ответ: х=8(12/25)=8,48.